PEMBERDAYAAN KADER KESEHATAN DALAM MEWUJUDKAN DESA PDKT (PEDULI KENDALI DIABETES) WILAYAH DESA SENDANGHARJO KECAMATAN BRONDONG KABUPATEN LAMONGAN - Su’udi,; Titik Sumiatin; Binti Yunariyah; Wahyu Tri Ningsih (Jurnal Abdi Masyarakat, 2026)
Diabetes mellitus (DM) remains a major challenge in the health sector due to the increasing prevalence and burden caused by DM (Sun et al., 2022). The goal of this community service activity is to enhance the role of health cadres in optimizing assistance in recognizing and controlling diabetes mellitus, creating a PDKT (Peduli Kendali Diabetes) Village in Lamongan Regency. The method used in this activity is training and mentoring health cadres in early diabetes detection. The target group is 26 health cadres in Sendangharjo Village, Brondong District, Lamongan Regency. The media used are the PDKT module and tools for early diabetes detection. The results of this activity are increased knowledge and skills of health cadres in early diabetes detection and the establishment of a PDKT (Peduli Kendali Diabetes) Post. Training and mentoring activities for cadres are carried out continuously to enhance their knowledge and skills.